2004
DOI: 10.1029/2002jc001687
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of suspended sediment on the ecosystem in Lake Michigan: A comparison between the 1998 and 1999 plume events

Abstract: [1] The impact of a reflective, recurrent coastal resuspension plume on the lower trophic food web system in Lake Michigan was examined using a 3-D coupled physical and biological model. Numerical experiments were conducted for the March 1998 and 1999 plume events. The comparison between modeling results of these 2 years shows that the spatial distributions of the biological fields (i.e., phosphorus, phytoplankton, detritus, etc.) were closely coupled to the physical environment associated with wind-induced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 27 publications
(35 reference statements)
2
50
0
Order By: Relevance
“…The RCP is an episodic event resulting from wind-driven sediment resuspension and transport in coastal waters (Chen et al, 2004). The feature has generally been observed to occur in late winter to early spring, which coincides with development of the spring diatom bloom.…”
Section: Abstract a Central Question Addressed By The Episodic Evenmentioning
confidence: 99%
See 2 more Smart Citations
“…The RCP is an episodic event resulting from wind-driven sediment resuspension and transport in coastal waters (Chen et al, 2004). The feature has generally been observed to occur in late winter to early spring, which coincides with development of the spring diatom bloom.…”
Section: Abstract a Central Question Addressed By The Episodic Evenmentioning
confidence: 99%
“…The El Niño (Kerr, 1998;McPhaden, 1999), which was accompanied by reduced ice cover and strong winter storms with winds out of the north that generated large waves (Beletsky et al, 2003). A series of studies demonstrated that the resultant resuspension event that occurred in 1998 was accompanied by reduced light availability for photosynthesis (Chen et al, 2004;Lohrenz et al, 2004;Vanderploeg et al, 2007).…”
Section: Abstract a Central Question Addressed By The Episodic Evenmentioning
confidence: 99%
See 1 more Smart Citation
“…These models range from historical water quality management models without physical dynamics (Chapra, 1977) to advanced three-dimensional physical models (Bai et al, 2013). Many threedimensional models are only presently set up for physical simulations, while others include biogeochemistry (Chen et al, 2004;Pauer et al, 2011) and carbon cycling (Bennington et al, 2012. Given the vast differences among the LGL, it is common that models are set up independently for each lake.…”
Section: Synthesis Findings and Remaining Gapsmentioning
confidence: 99%
“…FVCOM, an open-source 3D finite-volume model developed originally for ocean applications (Chen et al 2004(Chen et al , 2011, was used to represent the wind-driven circulation. The equations of mass, momentum, and temperature conservation, cast in a bottom following r-coordinate system, are given as:…”
Section: Computational Modelingmentioning
confidence: 99%